2018
DOI: 10.1200/jgo.17.00035
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Multicolor Melt Curve Analysis for High-Risk Human Papilloma Virus Detection in Low- and Middle-Income Countries: A Pilot Study for Expanded Cervical Cancer Screening in Honduras

Abstract: PurposeCervical cancer is a leading cause of cancer-related mortality in low- and middle-income countries (LMICs) and screening in LMICs is extremely limited. We aimed to implement on-site high-risk human papillomavirus (hrHPV) DNA testing in cohorts of women from an urban factory and from a rural village.MethodsA total of 802 women were recruited for this study in partnership with La Liga Contra el Cancer through the establishment of women’s health resource fairs at two locations in Honduras: a textile factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…We therefore developed a low-cost, simple DNA testing method for hrHPV using a crude cell lysate and real-time PCR instrument. 4,5 In several studies, we showed that hrHPV type distributions were more reflective of those found in Asia than in North America. 4,5,17 This geographically unexpected distribution underscores the need for HPV genotype surveillance to effectively triage hrHPV-positive participants for follow-up care and to strategize the implementation of successful vaccination programs.…”
Section: Introductionmentioning
confidence: 84%
See 3 more Smart Citations
“…We therefore developed a low-cost, simple DNA testing method for hrHPV using a crude cell lysate and real-time PCR instrument. 4,5 In several studies, we showed that hrHPV type distributions were more reflective of those found in Asia than in North America. 4,5,17 This geographically unexpected distribution underscores the need for HPV genotype surveillance to effectively triage hrHPV-positive participants for follow-up care and to strategize the implementation of successful vaccination programs.…”
Section: Introductionmentioning
confidence: 84%
“…Last, the low-cost DNA lysate and sensitive HPV assay described here allowed us to process 94 samples in less than 2.5 hours and return rapid genotype-specific results. This approach offers the following benefits: in contrast to other PCR-based assays that use hydrolysis probes, the equipment can be run off of a generator or variable power sources, as the system returns results despite power interruptions (Fig 4); the PCR system itself uses LEDs that require little, if any, maintenance; the DNA extraction method uses minimal and readily available disposables; lyophilized reagents were tested without refrigeration for 2 weeks and maintained their efficacy 4 ; and the combination of lyophilized reagents, crude lysate, and HPV genotyping performed by the instrument makes for an easy-to-perform operation that is suitable for testing in locations without highly trained personnel. These features allow for near-patient care diagnosis that is of critical importance for combining screening and treatment strategies in LMICs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2013, the CLARO team committed to an initial attempt to scale-up a PESCA screening, taking it farther afield into a rural mountainous region in Honduras, where cervical screening had been unavailable. 9 Previous community development work provided existing relationships, and local leaders were eager to host a free, large-scale cancer screening event for women that they determined should be called a "jornada" (Spanish for a day of work). Recognizing that this cancer screening jornada would be the first and potentially only cancer screening for recruited participants, it made sense to make the day as useful as possible, so low-tech breast cancer screening (ie, education and clinical examination) was coupled with cervical cancer screening.…”
Section: Methodsmentioning
confidence: 99%